Cybercrime awareness: development and evaluation of an adventure game / Aznoora Osman and Nurul Syarafina Azizan - Osman, Aznoora; Azizan, Nurul Syarafina (UiTM Cawangan Perlis, 2017)
This paper discusses the design and development of an adventure game about cybercrime. This game uses variety of multimedia elements including text, animation, image and 3D objects. The theme of this game focuses on identity theft and phishing. Therefore, the purpose of the game is to educate the learners about cybercrime and enhance their awareness towards online activities that could victimized them. This would ensure that they take precautions of their safety while using the Internet. In this research, agile method is used as the development methodology. It includes five phases which are brainstorm, design, development, quality assurance and deployment. The completed game was used as a treatment in a user testing involving 26 students from UiTM Cawangan Perlis from different ages, gender, course and faculty. After treatment, subjects were administered with two instruments to measure their perception of awareness towards cybercrime and their perception of fun for the game. It was revealed that most subjects agreed that they had an increase in awareness after exposure to the game. The game was also positively perceived as fun, with regards to its graphical and instructional design, contents relevance with the theme and suitability of game duration. Some recommendations for future enhancements are also discussed.